Book reviews (Czech Journal of International Relations, 1966)
The problems of compiling and evaluating the balance of payments in socialist countries are relatively neglected in socialist economic literature, and therefore it is necessary to evaluate positively that the seventh session of the Council of Social Sciences was devoted to them in the SAV Discussions. Even if at the present time, for various reasons, interest in issues of a financial and foreign exchange nature is increasing, discussions on these topics rarely appear, because contradictions and relationships from all the last areas of the national economy are projected into this area, so giving a summary explanation of these complex connections is very rare.